Evaluación Operativa De Colas En La Estación Aguacatala Del Metro De Medellín (2024)
The increase in the supply of services and the resulting queues at the Aguacatala station of the Medellín Metro highlights the importance of designing solutions that ensure efficient, comfortable, and safe circulation for users. The study presented in this document proposes to address this challenge by modeling the operation of the Aguacatala station, focusing specifically on queue management, using the Discrete Event Simulation (DES) methodology. The impact of the available services at the station is evaluated through a baseline scenario, measuring wait times and queue lengths on the platform. As a result, visual outputs are generated to identify under which situations wait times and crowding conditions would exceed certain thresholds.